In situ evaluation of a low fluoride concentration gel with sodium trimetaphosphate in enamel remineralization - Danelon, Marcelle [UNESP]; Takeshita, Eliana M. [UNESP]; Sassaki, Kikue T. [UNESP]; Carlos, Alberto [UNESP]; Delbem, Botazzo [UNESP] (My University, 2013)
Purpose: To evaluate the capability of gels with low fluoride (F) concentration and supplemented with sodium trimetaphosphate (TMP) to promote in situ enamel remineralization. Methods: Bovine enamel blocks were selected on the basis of their surface hardness after demineralization, and divided into five groups: gel without F or TMP (placebo); gel with 4,500 ppm F (4,500); gel with 4,500 ppm F + 5% TMP (4,500 5%TMP); gel with 9,000 ppm F (9,000) and gel with 12,300 ppm F (12,300). The study design was blind and cross-over: 12 subjects used palatal devices with four demineralized enamel blocks for 3 days, after topical fluoride application (TFA). Two blocks were removed immediately for analysis of the loosely bound fluoride (CaF2) and firmly bound fluoride (F) after TFA in enamel. In the remaining blocks, the percentage of surface hardness recovery (%SH), cross-sectional hardness (△KHN) and CaF2 and F were determined after remineralization. The results were subjected to ANOVA and Bonferroni tests (P< 0.05). Results: The groups 4,500 5%TMP, 9,000, and 12,300 showed the best results with regard to %SH (P< 0.05). Lower AKHN values were observed in the 4,500 5%TMP and 12,300 gel groups (P< 0.05). Higher concentrations of CaF2 and F were observed in the 12,300 group, followed by the 4,500 5%TMP and 9,000 groups (P> 0.05). It was concluded that it is possible to promote enamel remineralization using gels with low fluoride concentration supplemented with TMP.
Keywords: anticaries agent; calcium fluoride; fluoride; fluoride varnish; placebo; polyphosphate; trimetaphosphoric acid; adult; animal; biopsy; cattle; chemistry; comparative study; controlled clinical trial; controlled study; crossover procedure; dental procedure; drug combination; drug effect; enamel; gel; hardness; human; methodology; polarization microscopy; randomized controlled trial; single blind procedure; tooth disease; Adult; Animals; Biopsy; Calcium Fluoride; Cariostatic Agents; Cattle; Cross-Over Studies; Dental Enamel; Drug Combinations; Fluorides; Fluorides, Topical; Gels; Hardness; Humans; Microscopy, Polarization; Placebos; Polyphosphates; Single-Blind Method; Tooth Demineralization; Tooth Remineralization; Young Adult